Аналіз якості надання послуг гостинності популярними готелями Греції за критеріями оцінювання (на основі відгуків сайту Booking.com) - Круль, Галина Ярославівна; Заячук, Оксана Григорівна; Чорна, Богдана Віталіївна (Видавничий дім«Гельветика», Закарпатський угорський інститут імені Ференца Ракоці, 2025)
The relevance of the research. Guest satisfaction with the services provided by hospitality facilities is one of the most important aspects of the latter's operations, as it affects their image and financial stability. Taking into account the opinions of tourists, especially negative ones, expressed in the form of reviews on various online platforms, is a priority for hotel management. The subject of the research was negative feedback on hotel services in the most popular hotels in Greece according to Booking.com. The purpose of the study is to identify criteria for analyzing negative reviews of accommodation services in popular hotels in Greece in order to identify the biggest problems that cause them image and financial damage. Research methodology: analysis of literature sources, systematization and generalization of collected data. The results of the study. Based on the data from Booking.com, we have selected more than 1200 negative reviews regarding the stay in popular hotels in Greece, regardless of their category. The essence of the claims and wishes of the guests of hospitality establishments was analyzed. The article identifies 18 criteria by which most complaints about hotel services are recorded. In accordance with the criteria, the essence of the problems and the causes of their occurrence are clarified. It was found that most of the negative reviews relate to the location of hotels (distance from the sea), food services, room malfunctions, etc. Scope of the results application. The analysis of negative reviews in hospitality establishments in any country not only reveals problematic issues, but also directs the efforts of hotel management and owners to improve the image of the establishment and minimize financial losses. Conclusions. At a time when a guest's choice of a hotel is influenced by tourist reviews on various online platforms, their analysis and timely response to eliminate problems are extremely important for the successful operation of the hotel business. The prospect of further research is to analyze the feedback on hospitality services in the same hotels in Greece next season in order to identify hotel companies that have taken into account the recommendations of guests and improved hotel services.
Analysis of the quality of hospitality services provided by popular hotels in Greece according to the evaluation criteria (based on the reviews of Booking.com)
Keywords: готелі; послуги гостинності; негативні відгуки; готельний сервіс; якість обслуговування; критерії оцінювання готельних послуг